Justice: 1850s San Francisco and the California Gold Rush - Robinson, Paul H. (2015)
Using stories from the 1848-1851 California gold miners, the 1851 San Francisco vigilante committees, Nazi concentration camps of the 1940s, and wagon trains of American westward migration in the 1840s, the chapter illustrates that it is part of human nature to see doing justice as a value in itself—in people’s minds it is not dependent for justification on the practical benefits it brings. Having justice done is sufficiently important to people that they willingly suffer enormous costs to obtain it, even when they were neither hurt by the wrong nor in a position to benefit from punishing the wrongdoer.This is Chapter 4 from the general audience book Pirates, Prisoners, and Lepers: Lessons from Life Outside the Law (Potomac Books 2015). Included is a table of contents for the book and a summary of the line of argument of all of its chapters. (Chapter 3 of the book is also available on SSRN at http://ssrn.com/abstract=2413875)